Perceptions of faculty members at Yarmouk University about the possibility of applying VR technology in education - Yaqoup, Suheir Hamad (Journal of Educational and Psychological Sciences, 2022)
This study aimed to identify the perceptions of faculty members at Yarmouk University about the possibility of applying virtual reality (VR) technology in education. The study used the descriptive analytical method. The study tool consisted of a questionnaire consisting of (25) items distributed over four areas; It was applied to a random sample of (70) faculty members at Yarmouk University. The results indicated that the perceptions of faculty members at Yarmouk University about the possibility of applying virtual reality technology (VR) in education came with a total average (2.94 out of 5), i.e. with a degree of possibility (medium), at the level of sub- domains; The field of infrastructure got the highest arithmetic mean (3.21), then the field of human resources with an arithmetic mean (2.95), thirdly the field of students with an arithmetic mean (2.91), and fourthly the field of administrative legislation with an arithmetic mean (2.73), all of them with a degree of possibility (medium). The results also indicated that there were statistically significant differences at the level (α≤0.05) about the estimations of the sample members attributed to the variable of the country of graduation and in favor of the foreign country, and there were no differences due to the two variables (college and years of experience). Based on the results, the researcher made a number of recommendations to activate the application of VR technology in education at Yarmouk University and all Jordanian and Arab universities, in addition to proposals for future studies on the subject.